Forage intake and animal performance in Urochloa humidicola cultivars under continuous stocking - Martins, Clovis David Medeiros; Euclides, Valéria Pacheco Batista; Barbosa, Rodrigo Amorim; Montagner, Denise Baptaglin; Miqueloto, Tiago (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate forage accumulation, canopy structure, nutritive value, forage intake, and animal production in pastures of Urochloa humidicola under continuous stocking. The cultivars BRS Tupi and Comum were evaluated during the drought and wet periods (July 2011 to August 2012), in a randomized complete block experimental design, with two treatments and six replicates. Monthly, the animals were weighted and the pastures sampled for the determination of: forage accumulation rate (FAR); forage mass; percentages of leaves (PL), culms, and dead material (DL); and nutritive value. Forage intake (FI) was determined once a period. 'BRS Tupi' had a higher FAR, PL, and DL than 'Comum', during the wet period. The nutritive value, FI and the daily weight gain were similar between both cultivars. Forage protein content – 6.0 and 5.0%, for the wet and drought periods, respectively – was the main limiting factor for FI. 'BRS Tupi' had higher stocking rates and, consequently, made possible a higher live weight gain per area (192 kg ha‑1 per year) than 'Comum' (126 kg ha‑1 per year). 'BRS Tupi' is a good alternative for diversification of pastures in soils with low fertility that are temporarily subjected to flooding.